0\; ,\; \; t^2+t-1=0\; ,\; \; (t+0,5)^2-1,25=0\; ," alt="4^{1/x}+6^{1/x}-9^{1/x}=0\; ,\; \; x\ne 0\\\\(2^{1/x})^2+2^{1/x}\cdot 3^{1/x}-(3^{1/x})^2=0\; |:(3^{1/x})^2\ne 0\\\\t=(\frac{2}{3})^{1/x}>0\; ,\; \; t^2+t-1=0\; ,\; \; (t+0,5)^2-1,25=0\; ," align="absmiddle" class="latex-formula">
0\; \; ,\; \; t_2=-0,5-\sqrt{1,25}<0\; \; ne\; podxodit" alt="(t+0,5-\sqrt{1,25})(t+0,5+\sqrt{1,25})=0\\\\t_1=\sqrt{1,25}-0,5>0\; \; ,\; \; t_2=-0,5-\sqrt{1,25}<0\; \; ne\; podxodit" align="absmiddle" class="latex-formula">
![(\frac{2}{3})^{1/x}=\sqrt{\frac{125}{100}}-\frac{1}{2}\; ,\; \; (\frac{2}{3})^{1/x}=\frac{5\sqrt5}{10}-\frac{1}{2}=\frac{\sqrt5-1}{2} (\frac{2}{3})^{1/x}=\sqrt{\frac{125}{100}}-\frac{1}{2}\; ,\; \; (\frac{2}{3})^{1/x}=\frac{5\sqrt5}{10}-\frac{1}{2}=\frac{\sqrt5-1}{2}](https://tex.z-dn.net/?f=%28%5Cfrac%7B2%7D%7B3%7D%29%5E%7B1%2Fx%7D%3D%5Csqrt%7B%5Cfrac%7B125%7D%7B100%7D%7D-%5Cfrac%7B1%7D%7B2%7D%5C%3B%20%2C%5C%3B%20%5C%3B%20%28%5Cfrac%7B2%7D%7B3%7D%29%5E%7B1%2Fx%7D%3D%5Cfrac%7B5%5Csqrt5%7D%7B10%7D-%5Cfrac%7B1%7D%7B2%7D%3D%5Cfrac%7B%5Csqrt5-1%7D%7B2%7D)
![\frac{1}{x}=log_{2/3}\frac{\sqrt5-1}{2}\; ,\; \; x=\frac{1}{log_{2/3}\frac{\sqrt5-1}{2}} \frac{1}{x}=log_{2/3}\frac{\sqrt5-1}{2}\; ,\; \; x=\frac{1}{log_{2/3}\frac{\sqrt5-1}{2}}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7Bx%7D%3Dlog_%7B2%2F3%7D%5Cfrac%7B%5Csqrt5-1%7D%7B2%7D%5C%3B%20%2C%5C%3B%20%5C%3B%20x%3D%5Cfrac%7B1%7D%7Blog_%7B2%2F3%7D%5Cfrac%7B%5Csqrt5-1%7D%7B2%7D%7D)
![x=\frac{log_2\frac{2}{3}}{log_2(\sqrt{5}-1)-log_22}=\frac{1-log_23}{log_2(\sqrt5-1)-1} x=\frac{log_2\frac{2}{3}}{log_2(\sqrt{5}-1)-log_22}=\frac{1-log_23}{log_2(\sqrt5-1)-1}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7Blog_2%5Cfrac%7B2%7D%7B3%7D%7D%7Blog_2%28%5Csqrt%7B5%7D-1%29-log_22%7D%3D%5Cfrac%7B1-log_23%7D%7Blog_2%28%5Csqrt5-1%29-1%7D)